2021
DOI: 10.3390/adolescents1040034
|View full text |Cite
|
Sign up to set email alerts
|

School and Employment-Related Barriers for Youth and Young Adults with and without a Disability during the COVID-19 Pandemic in the Greater Toronto Area

Abstract: Purpose: Youth and young adults are particularly vulnerable to the socio-economic impacts of Coronavirus Disease (COVID-19). The purpose of this study was to explore barriers to school and employment for youth with and without a disability during the pandemic. Methods: This qualitative comparison study involved in-depth interviews with 35 youth and young adults (18 with a disability; 17 without), aged 16–29 (mean age 23). An interpretive, thematic analysis of the transcripts was conducted. Results: Our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
2
16
0
1
Order By: Relevance
“…The context of the COVID-19 pandemic also reduced opportunities related to job search and availability of work for young adults during a critical life stage of entry into the labour market ( OECD, 2021c ). Qualitative explorations have indicated that these economic disruptions represented major concerns for young adults who reported increasing feelings of precarity, financial strain, and uncertainty about their career development ( Burgess et al, 2022 ; Lindsay & Ahmed, 2021 ). These experiences of emotional stress due to the COVID-19-induced economic crisis represent critical risk factors for mental health challenges ( Achdut & Refaeli, 2020 ; de Miquel et al, 2022 ; Graupensperger et al, 2022 ; Ranta et al, 2020 ; Shanahan et al, 2022 ), including depression, the prevalence of which has steadily increased among young adults in recent decades ( Mojtabai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The context of the COVID-19 pandemic also reduced opportunities related to job search and availability of work for young adults during a critical life stage of entry into the labour market ( OECD, 2021c ). Qualitative explorations have indicated that these economic disruptions represented major concerns for young adults who reported increasing feelings of precarity, financial strain, and uncertainty about their career development ( Burgess et al, 2022 ; Lindsay & Ahmed, 2021 ). These experiences of emotional stress due to the COVID-19-induced economic crisis represent critical risk factors for mental health challenges ( Achdut & Refaeli, 2020 ; de Miquel et al, 2022 ; Graupensperger et al, 2022 ; Ranta et al, 2020 ; Shanahan et al, 2022 ), including depression, the prevalence of which has steadily increased among young adults in recent decades ( Mojtabai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…F riences of youth with disabilities. Other research on employment has found that young people with disabilities were disproportionately affected by the pandemic [74,83]. Future research should explore how pandemic-related workplace changes affected youth and young adults, since few studies focused on this age group.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
“…The employment rate for people with disabilities has decreased at nearly double the rate compared with people without disabilities (Schur et al, 2020). Some individuals with disability, such as those with physical disabilities, encountered reduced access to necessary work-related transportation and assistance during the COVID-19 pandemic (Cochran, 2020), while others who may have had the opportunity to engage in remote work lacked the resources necessary to make this transition due to disproportionate financial burdens (Lindsay & Ahmed, 2021).…”
Section: People With Disabilitiesmentioning
confidence: 99%
“…The intersectional concern of socioeconomic access to the resources necessary for remote work must also be acknowledged to ensure these transitions are managed equitably. While some people with disabilities may have the preestablished resources necessary to engage in remote work, others may face a much higher upfront cost in making the transition to remote work (Lindsay & Ahmed, 2021). Additionally, gig work, an area of the workforce noted to be particularly beneficial to people with disabilities due to its inherent flexibility, has received a greater focus due to the COVID-19 crisis and may see greater regulation in the form of legal protections and worker benefits (Harpur & Blanck, 2020).…”
Section: People With Disabilitiesmentioning
confidence: 99%